2015
DOI: 10.1140/epjb/e2015-50720-7
|View full text |Cite
|
Sign up to set email alerts
|

The question of intrinsic origin of the metal-insulator transition in i-AlPdRe quasicrystal

Abstract: The icosahedral (i-) AlPdRe is the most resistive quasicrystalline alloy discovered so far. Resistivities (ρ) of 1Ωcm at 4K and correlated resistance ratios (RRR = ρ4K /ρ300K ) of more than 200 are observed in polycrystalline samples. These values are two orders of magnitude larger than for the isomorphous i-AlPdMn phase. We discuss here the controversial microscopic origin of the i-AlPdRe alloy electrical specificity. It has been proposed that the high resistivity values are due to extrinsic parameters, such … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Experimental investigations have indicated that the conduction properties of many stable quasicrystals (AlCuFe, AlPdMn, AlPdRe, ...) are unusual and differ strongly from those of simple inter-metallic alloys [1][2][3]. In particular their conductivity increases with static defects density and when temperature increases.…”
mentioning
confidence: 99%
“…Experimental investigations have indicated that the conduction properties of many stable quasicrystals (AlCuFe, AlPdMn, AlPdRe, ...) are unusual and differ strongly from those of simple inter-metallic alloys [1][2][3]. In particular their conductivity increases with static defects density and when temperature increases.…”
mentioning
confidence: 99%
“…To resolve this issue, we used the data available in the literature for Al-Pd-Re materials, monocrystalline with σ 0 ∼ 176 (Ω cm) -1 [14] and amorphous with σ 0 ∼ 1470 (Ω cm) -1 [15], i.e., for dense materials morphologically different from polycrystals [1][2][3][4][5]. The corresponding curves are shown in Figs.…”
Section: Experimental Justificationmentioning
confidence: 99%
“…After thirty years of intensive research, variable range hopping (VRH) conductivity has become the focus of violent polemics about the intrinsic and nonintrinsic properties of quasicrystals [1][2][3][4][5][6]. This is not accidental.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4. Chemical trends in the low-temperature electrical resistivity ( ) and the electrical resistivity ratio (R) defined as R = (4 K)/ (300 K) of Al-based i-QCs [57,[69][70][71][72][73][74][75]. The electrical resistivity trends illustrated in Table 4 may arise from the relativistic contraction of the s and p states relative to the d and f ones, which lowers the orbital energies of the former and screens the nucleus effective charge, so that the outer d electrons experience a lesser binding, hence displaying a larger spatial extent.…”
Section: Chemical Fingerprints In the Physical Propertiesmentioning
confidence: 99%